Beyond "Peak Car": A reflection on the evolution of public sentiment about the role of cars in cities. (March 2017) - Lee-Gosselin, Martin E.H.
Abstract: In this volume, Jones has made a persuasive case for considering recently observed reductions in car use (and sometimes car ownership) in a number of major northern cities as part of an evolutionary process, rather than the consequence of transient conditions such as the economic downturn of 2008 and its relatively slow recovery. In an era bringing new service models for mobility and communications that have important implications for safety, security, the environment and well-being, he points to the role of public attitudes and sentiments that may underlie changing policy priorities and an associated culture change with respect to transport in cities and the reclamation of street space. This paper briefly explores the role of public sentiments and reflects on the apparent emergence of a popular subculture that favors living, if possible, without owning or using cars, in contrast to older subcultures embracing more extreme sentiments that are either Car-centered or emphatically anti-car.